Perbandingan SAK-ETAP dengan penyajian laporan keuangan koperasi: Studi kasus pada Koperasi ABC - Julyanne Gracia Irawan; Ibnu Aswat; Vitriyan Espa (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2024)
Financial reports are a crucial aspect of business sustainability, especially in cooperative businesses, as they enhance the quality of financial reports by adhering to accounting standards. This study aimed to compare the Financial Accounting Standards for Entities Without Public Accountability (SAK-ETAP) with the financial statements of ABC savings and loan cooperatives in Pontianak. The qualitative method involved three approaches: interviews (in-depth interviews), documentation, and literature review. The study results revealed significant differences between the financial statements of ABC Cooperative and the Financial Accounting Standards for Entities Without Public Accountability (SAK-ETAP). It was found that the presentation of financial statements by ABC Cooperative did not fully comply with the SAK-ETAP. Public interest statements This study is evidenced by the lack of adjustments to items in the presentation of financial statements and the absence of reports presented in the form of statements of changes in equity, flow statements, and notes to the financial statements. These findings indicate that ABC Cooperative's financial statements may not be effectively utilized by relevant parties for business sustainability planning.